Sex differences in outcomes of late-Window Endovascular Stroke Therapy - Abdalkader, Mohamad; Ning, Shen; Qureshi, Muhammad M.; Haussen, Diogo C.; Strbian, Daniel; Nagel, Simon; Demeestere, Jelle; Pütz, Volker; Mohammaden, Mahmoud H.; Olive Gadea, Marta; Winzer, Simon; Yamagami, Hiroshi; et al. (Stroke, 2024)
BACKGROUND: - The association between sex and outcome after endovascular thrombectomy of acute ischemic stroke is unclear. The aim of this study was to compare the clinical and safety outcomes between men and women treated with endovascular thrombectomy in the late 6-to-24-hour window period. - METHODS: - This multicenter, retrospective observational cohort study included consecutive patients who underwent endovascular thrombectomy of anterior circulation stroke in the late window from 66 clinical sites in 10 countries from January 2014 to May 2022. The primary outcome was the 90-day ordinal modified Rankin Scale score. Secondary outcomes included 90-day functional independence (FI), return of Rankin (RoR) to prestroke baseline, FI or RoR, symptomatic intracranial hemorrhage, and mortality. Multivariable and inverse probability of treatment weighting methods were used. We explored the interaction of sex with baseline characteristics on the outcomes ordinal modified Rankin Scale and FI or RoR. - RESULTS: - Of 1932 patients, 1055 were women and 877 were men. Women were older (77 versus 69 years), had higher rates of atrial fibrillation, hypertension, and greater prestroke disability, but there was no difference in baseline National Institutes of Health Stroke Scale score. Inverse probability of treatment weighting analysis showed no difference between women and men in ordinal modified Rankin Scale (odds ratio, 0.98 [95% CI, 0.79-1.21]), FI or RoR (odds ratio, 0.98 [95% CI, 0.78-1.22]), severe disability or mortality (odds ratio, 0.99 [95% CI, 0.80-1.23]). The multivariable analysis of the above end points was concordant. There were no interactions between baseline characteristics and sex on the outcomes of ordinal modified Rankin Scale and FI or RoR. - CONCLUSIONs: - In late presenting patients with anterior circulation stroke treated with endovascular thrombectomy in the 6 to 24-hour window, there was no difference in clinical or safety outcomes between men and women.